Cumulative incidence and risk of infection in patients with rheumatoid arthritis treated with janus kinase inhibitors: A systematic review and meta-analysis. - Konstantinos Ouranos; Diana V Avila; Evangelia K Mylona; Athanasios Vassilopoulos; Stephanos Vassilopoulos; Fadi Shehadeh; Eleftherios Mylonakis (PLoS ONE)
Patients with rheumatoid arthritis (RA) who receive immunosuppressive medications have a heightened risk of infection. The goal of our study was to calculate the pooled cumulative incidence and risk of infection in patients with RA treated with Janus kinase inhibitors (JAKi). The PubMed and EMBASE databases were queried for randomized controlled trials comparing patients with RA treated with JAKi (upadacitinib, baricitinib, tofacitinib, peficitinib, or filgotinib), defined as the treatment group, compared with control subjects, defined as participants receiving placebo or treatment regimen that was similar to that of participants in the treatment group, with the exception of JAKi. The primary study endpoint was the relative risk (RR) of any-grade and severe infection. The secondary endpoints were RR and cumulative incidence of opportunistic infections, herpes zoster, and pneumonia. The Stata v17 software was used for all data analysis. Results showed that treatment with baricitinib was associated with an increased risk of any-grade (RR 1.34; 95% CI: 1.19-1.52) and opportunistic (RR 2.69; 95% CI: 1.22-5.94) infection, whereas treatment with filgotinib (RR 1.21; 95% CI: 1.05-1.39), peficitinib (RR 1.40; 95% CI: 1.05-1.86) and upadacitinib (RR 1.30; 95% CI: 1.09-1.56) was associated with increased risk of any-grade infection only. Analysis based on type of infection showed a pooled cumulative incidence of 32.44% for any-grade infections, 2.02% for severe infections, 1.74% for opportunistic infections, 1.56% for herpes zoster, and 0.49% for pneumonia in patients treated with any JAKi during the follow-up period. Treatment with specific JAKi in patients with RA is associated with an increased risk of any-grade and opportunistic infections but not severe infection. Close clinical monitoring of patients with RA treated with JAKi is required to establish the long-term infection risk profile of these agents.